Routine Screening with Contrast Echocardiography in Apical Infarctions? A case report - Siniscalchi, Carmine; Gaibazzi, Nicola (Acta Biomedica Atenei Parmensis, 2021)
A a 80-year-old male underwent routine transthoracic echocardiography the day after primary percutaneous revascularization procedure for ST-elevation myocardial infarction. When ultrasound contrast was injected, regular contrast-enhancement of the left ventricle (LV) excluded the presence of thrombus. A second echocardiogram, performed four months later, showed a hyperechoic image in the LV apex, which was confirmed after contrast injection as a thrombus. Four weeks later, a third follow-up echocardiogram appears apparently normal. However, contrast injection clearly demonstrates a new apex thrombus, in a slightly different location from the one detected previously. Standard echocardiography is often inconclusive or falsely negative regarding the detection of apical thrombus. Maybe the time has come for routine contrast-echo screening in post-myocardial infarction patients with the high likelihood of thrombus, such as in cases of apical infarction, even if the standard echocardiogram appears unremarkable.